Filmy aktorskie o przygodach Asteriksa i Obeliksa jako przejaw obecności antyku we współczesnej kulturze audiowizualnej - Stawiski, Maciej (Collectanea Philologica, 2015)
The films with actors about the adventures of Asterix and Obelix are an important partof the contemporary popular culture. The plot of these film is located in antiquity therefore ancientmotives are common in them. It is very important to check if these motives are showed in the waywhich is consistent with historical truth. And it is very important to know how big their influenceon popular perception on antiquity is. This article is a first step to answer these questions. It showsthat some motives are showed correctly but some are presented incorrectly. It suggests also that somepeople may see druids through the prism of these films.